2001
DOI: 10.1039/b101493p
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in bone lead concentration: implications for modelling of human bone lead metabolism

Abstract: In this study, 539 occupationally exposed subjects received in vivo bone lead measurements using 109Cd excited K X-ray fluorescence (109Cd K XRF). Of these subjects, 327 had previously been measured five years earlier. Measurements were made from both tibia and calcaneus samples, taken to reflect cortical and trabecular bone, respectively. Changes in tibia lead concentration related negatively to initial tibia lead concentration and positively to both lead exposure between the measurement dates and initial cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…As a matter of fact, if only the estimated contrasts in bone resorption between actually exposed groups in this study were considered, then the current results would suggest that decreasing OC levels favor the increment of the halflife of Pb in bone with increasing exposure. This is consistent with the conclusion that the half-life of Pb in bone is increased at higher exposure, established in previous work based on a sample 75% of which were Pb exposed subjects older than 40 years [8], and therefore with OC expectedly at the lowest levels according to published data [42]. As a final remark, such consistency is not undermined by the lack of statistical significance of the estimated contrasts in bone resorption between exposed groups in this work , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 because even with a much larger sample not all half-life contrasts for compact and trabecular bone reach the traditional 5% level of significance [8].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As a matter of fact, if only the estimated contrasts in bone resorption between actually exposed groups in this study were considered, then the current results would suggest that decreasing OC levels favor the increment of the halflife of Pb in bone with increasing exposure. This is consistent with the conclusion that the half-life of Pb in bone is increased at higher exposure, established in previous work based on a sample 75% of which were Pb exposed subjects older than 40 years [8], and therefore with OC expectedly at the lowest levels according to published data [42]. As a final remark, such consistency is not undermined by the lack of statistical significance of the estimated contrasts in bone resorption between exposed groups in this work , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 because even with a much larger sample not all half-life contrasts for compact and trabecular bone reach the traditional 5% level of significance [8].…”
Section: Discussionsupporting
confidence: 93%
“…In view of current assumptions in PBKM, namely that Pb is incorporated in bone during bone formation and is removed from bone during bone resorption [3,4], it seems paradoxical that both osteopenia and increased half-life of Pb in bone, as suggested in this work and observed in previous studies [7,8], respectively, are apparently associated with higher exposures to Pb. This apparent paradox, however, can be explained by the methodological options of data analysis followed in this and previous studies.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…51,52 Following improvements in industrial hygiene, tibia Pb concentrations in 51 subjects had fallen to a mean of 33 mg g bone mineral 21 from a mean of 39 mg g bone mineral 21 in a previous study five years earlier. However, surprisingly, calcaneous Pb had not fallen significantly from a level of 64 mg g bone mineral 21 .…”
Section: Fundamental Developments In In Vivomentioning
confidence: 99%
“…It was found that subjects with higher bone Pb had significantly slower release rates of Pb from bone. When a different comparison was made within the overall group, it was found that older subjects released Pb from bone more slowly than did younger people 33) . Within this overall study, as within nearly all similar groups, bone Pb correlates strongly with age for two reasons.…”
mentioning
confidence: 99%